PENERAPAN STRATEGI PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 21 BALAI MAKAM KECAMATAN MANDAU - Asnirayani '; Zariul Antosa; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem this research is the student achievement of sciences studies three graderes SDN 21 Balai Makam still low with an average value of 60,5 and minimum completenness criteria (KKM) sciences studies is 70. Between students, amounting to 30 people only 12 students who achieve classical KKM with 40%. This research is Classroom action Research (CAR), wich aims to improve the learning process in the classroom. Formulation of the problem : is the implementation of learning strategy incury can improve students achievment of sciences studies at SDN 21 Balai Makam Kecamatan Mandau. The research was conducted on April 6, 2016 to Mei 11, 2016 by 2 cyclees. Subjects were students of SDN 21 Balai Makam Kecamatan Mandau, totalling 30 people who use the data source. The data collection instruments in this research is a teacher and students activities sheets and students achievement. Based on the conduct of research with the implementation of learning strategi incuiry of activity the teacher in the lerning process in cycle I frist meeting was 58,33% and at the second meeting of teacher activity increased by 12,5% to 66,67%. cycle II firs meeting and the second meeting of activity increased by 23,8% to 87,50% and the second meeting of activity increased by 14,9% to 95,83%. Result of data analysis of students activities in the first meeting cycle with the first meeting of an avarage of 50% and at second meeting of activity increased 14,3% to 58,33%% and a second meeting of activity increased 26,3% improve to 79,17%. At the firs meeting of the second meeting of activity increased 13,6% to 91,67%%. This research presents the results obtained each before the implementation an improve in base score sycle with the average being, 60,5. In the first cycle improve an average of 63,8 with increase as 5,5% and an impove in the second with an average of 73,3 with increase as 21,2%. Result in the research that the implementation of learning strategy incuiry can improve students achievement of sciences Studies at three graderes SDN 21 Balai Makam Kecamatan Mandau. Key Words : Strategy Learning Incuiry, learning outcomes IPA.